1993
DOI: 10.1037/0022-0663.85.3.446
|View full text |Cite
|
Sign up to set email alerts
|

Classroom racial proportions and children's peer relations: Race and gender effects.

Abstract: Peer preferences (determined by both positive and negative sociometric choices) and perceptions of African-American and White children attending either majority White or majority African-American classrooms were examined. Results indicate that classroom racial minority status (i.e., being in a classroom in which most classmates are of a different race) is associated with peer rejection of girls but not of boys. Correlates of peer preferences differed for children in majority White versus African-American class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 18 publications
4
60
0
1
Order By: Relevance
“…Indeed, other work suggests that White children in more ethnically balanced classrooms tend to be more positive in their assessment of non-White children than those in White-only or predominantly White classes (see Aboud, 1988;Cohen, 1980;Kistner, Metzler, Gatlin, & Risi, 1993;Schofield & Sagar, 1977).…”
Section: The Possible Confound Of Classroom Ethnic Compositionmentioning
confidence: 99%
“…Indeed, other work suggests that White children in more ethnically balanced classrooms tend to be more positive in their assessment of non-White children than those in White-only or predominantly White classes (see Aboud, 1988;Cohen, 1980;Kistner, Metzler, Gatlin, & Risi, 1993;Schofield & Sagar, 1977).…”
Section: The Possible Confound Of Classroom Ethnic Compositionmentioning
confidence: 99%
“…A study by Kistner et al (1993) asserted that research into interethnic bias in multicultural classrooms should not only focus on the students' ethnic status in terms of majority or minority per se, but should also focus on the relative majority/minority ratio in a specific classroom. Bellmore, Witkow, Graham, and Juvonen (2004) provided evidence that pupils' relative ethnic status is related to maladjustment: pupils in a majority in their class but in a minority in society generally showed more maladaptive behaviour than pupils who were in a minority both in the classroom and in society generally.…”
Section: Discussionmentioning
confidence: 99%
“…An American study by Coie, Dodge, and Copotelli (1982) suggested that immigrant students in general are less popular than white pupils since they form a minority group (see also Kistner, Metzler, Gatlin, & Risi, 1993). We argue that with prolonged exposure to SCL the popularity of immigrant pupils increases, as compared to that of non-immigrant pupils.…”
Section: Operationalizing Interethnic Biasmentioning
confidence: 99%
“…Some have found that males of both races are more likely to interact across racial lines (Schofield 1982;Schofield and Sager 1977), while others have found that it is white females who are most likely to do so (Damico and Sparks 1986). Some studies have found that African American females are less likely to have interracial interactions or friendships in comparison to African American males (Damico and Sparks 1986;Eaton 2001;Ispa-Landa 2009;Kitsner et al 1993), while studies focusing more broadly on crossing social boundaries have tended to find that African American females are more willing and/or able to engage in different interaction styles to facilitate this crossing. African American females were found to be most likely compared to white females and African American and white males to act as ''go-betweens'' in elementary classrooms, interacting across race, age, and gender boundaries (Grant 1984).…”
Section: Gender Differences In Integrationmentioning
confidence: 99%
“…Studies of friendship patterns tend to neglect the role of status as a multidimensional concept in determining a student's position in the social network. Status, when included, is usually operationalized as academic ability or racial minority status (see Kitsner et al 1993). Status among youth can be seen as a reflection of parents' socioeconomic status (Gaines 1991;Hollingshead 1950), but many other elements can affect a student's status within his or her peer culture, such as athleticism and participation in extracurricular activities Coleman 1961;Eder and Kinney 1995;Goto 1997;Kinney 1993) as well as attractiveness, social skills, and personality (Coleman 1961;Kinney 1993).…”
Section: Social Integrationmentioning
confidence: 99%